2006
DOI: 10.1097/01.ta.0000222669.09582.ec
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Thoracic Spine Stabilization in Trauma Patients: Impact on Clinical Course and Outcome

Abstract: Almost 10% of all patients in the German National Trauma Registry had severe spine injuries. Severe thoracic injuries occurred in 95% of these patients with thoracic spine trauma. We provide further evidence that early stabilization of thoracic spine injuries in trauma patients reduces overall hospital and ICU stay and improves outcome. Thus early stabilization of thoracic spine injuries within 3 days after trauma appears to be favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…exposure of the spine, with prolonged operative times and profuse intraoperative blood loss [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…exposure of the spine, with prolonged operative times and profuse intraoperative blood loss [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Croce data underline as an early spine fixation at every level, is associated to a lower incidence of venous thrombosis, distress respiratory syndrome and H-LOS [5]. Schlegel showed as a delayed treatment after 72 h from trauma is associated to an increased pneumonia incidence risk till to 12.2 time, 4.8 time pressure sores onset risk, 3.2 time urinary tract infection risk of this of early fixation patients [10]. Patients underwent to delayed spine fixation showed also an increased mechanical ventilation need.…”
Section: Discussionmentioning
confidence: 98%
“…In our series better results were obtained in the most injured patients, belonging to the III and IV SAPS II score quartile. Sickest patients benefit more from early surgical treatment [10]. The clinical outcome of patients with vertebral fractures is influenced not only from the timing of surgical treatment but also from fracture level and trauma severity, throughout an early treatment largely contributes to the decrease of comorbidities in severe injured patients [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 22 clinical studies identified in this review, nine Level III studies measured the length of stay [7,11,14,16,27,32,37,40,42,52]. Early surgical decompression was associated with a shorter hospital length of stay in eight studies [7,14,16,27,32,37,40,42] (although Guest et al [27] reported no p values), whereas the other only recorded the length of stay in the ICU [52]. A subset of these studies further divided overall length of stay with the duration of stay in the ICU [14,16,27,32] and found this time point was also less in patients receiving early decompressive surgery.…”
Section: Histopathologic Correlationmentioning
confidence: 99%